Risk and preventive factors for adolescent drug use in Iceland - Sigurbjörg Eva Helgadóttir 1998- (2021)
Although many studies on adolescent substance use have shown similar preventive and risk factors, there are studies that show contradicting results regarding the effectiveness of preventive factors. This study sought to answer whether adolescents who practice organized sports or leisure activities, or who experience parental affection and supervision, are less likely to use drugs; and whether adolescents with the following characteristics are likelier to use drugs: being of a single-parent household, having attention deficit hyperactivity disorder (ADHD), having experienced sexual abuse, having experienced physical abuse, or feeling lonely. The sample used for this quantitative cross-sectional analysis was of 2,072 students in high schools in Iceland. Results from Analysis of Variance and Multiple Linear Regression showed that parental affection and supervision proved to be significant preventive factors against substance use, and that sexual abuse, loneliness, having ADHD, and being of a single-parent household (only when living with a single mother, not father) are significant risk factors for substance use. A significant association was not found between substance use and engaging in sports and organized leisure activities or having experienced physical abuse. Results emphasize the importance of intervention for at-risk youth, along with implementation of preventive factors for the general adolescent population. Keywords: adolescents, substance use, preventive factors, risk factors, Icelandic youth Fjöldi rannsókna hafa sýnt svipaðar niðurstöður hvað varðar áhættu- og verndandi þætti fyrir vímuefnaneyslu unglinga, en þó eru rannsóknir sem sýna ólíkar niðurstöður varðandi áhrifa verndandi þátta. Markmið rannsóknarinnar er að kanna hvort unglingar sem upplifa umhyggju og eftirlit frá foreldrum og unglingar sem stunda skipulagt íþrótta- og tómstundastarf séu ólíklegri til að neyta vímuefna og hvort unglingar með eftirfarandi einkenni séu líklegri til þess að neyta vímuefna: búa með einstæðu foreldri, eru með ...